2009
DOI: 10.1179/146580109x12540995045886
|View full text |Cite
|
Sign up to set email alerts
|

Design of experiment study of compression moulding of SMC

Abstract: The effect of vacuum assistance, mould temperature and ram velocity on the void transport and flow behaviour for sheet moulding compound (SMC) have been investigated with a design of experiment approach of the compression moulding phase. The relative amount of voids has been quantified with a high voltage insulation test and the flow behaviour has been quantified with image analysis of samples moulded with coloured SMC. In conclusion, the setting of high vacuum, low ram velocity and low mould temperature creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Different speeds and temperatures of the plates were used and the uneven flow was captured by video recordings of the flow front as shown in Figure 2 for a relatively low speed of 2 mm/s, an lower plate temperature of 135 • C and an upper plate temperature of 165 • C. It should be noted that the compound starts to flow near the lower plate as it had been subjected to heat for a longer time. This phenomenon was first observed by Barone [8] from partial moldings and later confirmed by molding using sheets of varying color by Olsson [9], where it is obvious that the outer layers end up at the flow front. Hence, the outer layers do not stay as outer layers which results in a complicated three-dimensional flow in the front of the SMC during pressing.…”
Section: Phenomenological Description Of the Processsupporting
confidence: 52%
See 2 more Smart Citations
“…Different speeds and temperatures of the plates were used and the uneven flow was captured by video recordings of the flow front as shown in Figure 2 for a relatively low speed of 2 mm/s, an lower plate temperature of 135 • C and an upper plate temperature of 165 • C. It should be noted that the compound starts to flow near the lower plate as it had been subjected to heat for a longer time. This phenomenon was first observed by Barone [8] from partial moldings and later confirmed by molding using sheets of varying color by Olsson [9], where it is obvious that the outer layers end up at the flow front. Hence, the outer layers do not stay as outer layers which results in a complicated three-dimensional flow in the front of the SMC during pressing.…”
Section: Phenomenological Description Of the Processsupporting
confidence: 52%
“…Similar experiments have since been conducted by Olsson et al [9]. An important conclusion drawn by Olsson et al [9] is that a higher mold closing speed resulted in a more homogeneous flow, while a lower closing speed resulted in more mixing between the layers of the charge. Important early numerical work was performed by Tucker et al [10] and Lee et al [11], who developed a model for the flow of the charge based on Hele-Shaw flow (see for instance [12]).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Afterwards void gas mass variation due to diffusion only is determined thanks to Eq. (18). Another loop stop is introduced in order to verify if the new gas mass inside void is positive.…”
Section: Coupled Visco-mechanical and Gas Diffusion Void Growth Modelmentioning
confidence: 99%
“…Several authors have reported the influence of the manufacturing process on void content: for Resin Transfert Molding [12][13][14][15][16][17] (RTM), Sheet Moulding Compound (SMC) [18][19][20], or autoclave [21][22][23] processes.…”
Section: Introductionmentioning
confidence: 99%